1996
DOI: 10.1080/03014223.1996.9518086
|View full text |Cite
|
Sign up to set email alerts
|

Control of a stoat (Mustela erminea) population irruption to enhance mohua (yellowhead) (Mohoua ochrocephala) breeding success in New Zealand

Abstract: The mohua or yellowhead (Mohoua ochrocephala) is an endangered, hole-nesting forest bird endemic to New Zealand. Mohua suffer periodic population crashes due to severe predation by the introduced stoat (Mustela erminea). In 1990, a stoat population irruption provided an opportunity to reassess the impact of stoat predation on mohua and to test two linked hypotheses: that adaquate control of stoats by trapping is possible, and that it is a viable management option to assist mohua recovery. The primary experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 12 publications
1
36
0
Order By: Relevance
“…King (1983) quantified the link between heavy beech seedfall and stoat population irruptions, and Elliott & O'Donnell (1988), Elliott (1990), andO'Donnell et al (1992) indicated that mohua suffer periodic population crashes which coincide with these stoat irruptions in the Hawdon and Eglinton Valleys. Results of the monitoring programme indicate that this process is probably widespread throughout the mohua's range.…”
Section: Results Of the Monitoring Programmementioning
confidence: 99%
See 2 more Smart Citations
“…King (1983) quantified the link between heavy beech seedfall and stoat population irruptions, and Elliott & O'Donnell (1988), Elliott (1990), andO'Donnell et al (1992) indicated that mohua suffer periodic population crashes which coincide with these stoat irruptions in the Hawdon and Eglinton Valleys. Results of the monitoring programme indicate that this process is probably widespread throughout the mohua's range.…”
Section: Results Of the Monitoring Programmementioning
confidence: 99%
“…The largest between-year declines in mohua numbers coincided with population irruptions of stoats following heavy beech seeding (see Elliott & O'Donnell 1988;Elliott 1990;O'Donnell et al 1992). These were between in Hawdon Valley, between 1987and 1988in Eglinton Valley, and between 1990and 1991 Of the three sites where some stoat trapping was undertaken, one continued to decline (Hawdon Valley) and two remained stable (Mt Stokes, Eglinton Valley).…”
Section: Catlins Forest South Otago (Nzms 260 G46)mentioning
confidence: 99%
See 1 more Smart Citation
“…Native fauna in New Zealand forests are at risk from predation by introduced mammals, especially the ship rat (Rattus rattus), and the stoat (Mustela erminea) (Innes & Hay 1991;King et al 1996;O'Donnell et al 1996). Large-scale poisoning by aerial application or bait stations is used routinely to control rats and another pest species, the Australian brushtail possum (Trichosurus vulpecula) New Zealand Journal of Zoology, 1998, Vol.…”
Section: Introductionmentioning
confidence: 99%
“…During the summers of 1987/88 and 1990/91, there were stoat irruptions in Eglinton Valley, and consequent high rates of predation of mohua nests (Elliott 1990;O'Donnell et al 1996). During these years, successful nests were higher above the ground than failed ones (Table 1; P = 0.016), and more often in red beech than silver beech (x 2 = 4.571, d.f.…”
Section: Comparison Of Successful and Unsuccessful Nest Sitesmentioning
confidence: 99%